EFFECTS OF PLANTING PATTERNS AND IRRIGATION CONDITIONS ON THE PHOTOSYNTHETIC CHARACTERISTICS OF WINTER WHEAT - Z. B. Feng; X. Y. Wang; X. B. Zhou; Y. H. Chen; J. J. Bi (Journal of Animal and Plant Sciences, 2014)
The effects of irrigation and planting pattern on wheat in field conducted at Taian, northern China during 2011-12. The experiments consisted of two planting patterns (single and double rows) and two irrigation levels (0 and 180 mm) resulting in the same plant density (200 × 104 plant/ha). Each experiment plot was 3 m × 3 m in size and replicated thrice in split-plot design. During course of study net photosynthetic rate, H2O conductance, transpiration rate, and maximum photochemical efficiency of flag leaves and grain yield of winter wheat were recorded. At the maturity stage, the net photosynthetic rate of the plants grown in a double-row planting pattern was higher than that of the plants grown in a single-row planting pattern without irrigation. H2O conductance and transpiration rate of plants in the double-row planting pattern were higher than those grown in the single-row planting pattern without and with irrigation. The double-row planting pattern exhibited higher capacity utilization to high light and higher resistivity to photo inhibition than the single-row planting pattern. The spike number per square meter of the double-row planting pattern was higher than that of the single-row planting pattern under the same water treatment. The 1000-kernel weight of the non-irrigated plants grown in the double-row planting pattern was higher than that in the single-row planting pattern. Hence, the double-row planting pattern improved the photosynthetic capacity of winter wheat under water stress (non-irrigated plants).
Keywords: Triticum aestivum; net photosynthetic rate; light response curve; photochemical efficiency; yield